Eco-friendly Powder Sunscreen Combining Kaolin and Zinc Oxide with Determination of Sun Protection Factor - Aspadiah, Vica; Sahumena, Muhammad Handoyo; Suryani, Suryani; Muliadi, Rahmat; Sinta, Dwi (Universitas Muhammadiyah Prof. DR. HAMKA, 2026)
Excessive exposure to UV radiation can cause skin damage, making sunscreen use necessary. However, chemical ingredients may have negative impacts on marine ecosystems. Therefore, an eco-friendly powder sunscreen combining kaolin and zinc oxide was developed. This study aimed to determine the formulation, evaluate the physical characteristics, and assess the effectiveness of UV protection by determining the SPF value. The study used a mixing method followed by physical characteristic testing, including organoleptic evaluation, pH measurement, homogeneity, adhesion, moisture content, fineness degree, and SPF determination using a UV-Vis spectrophotometer. The results showed that the combination of kaolin and zinc oxide produced a formula with good physical characteristics, including a light brown colour, a distinctive odour, a smooth and homogeneous texture, a pH ranging from 6.78 to 7.29, adhesion ranging from 82% to 90%, moisture content ranging from 0.05% to 0.25%, a powder fineness of 95%, and SPF values ranging from 13.69 to 16.01. The best formulation was Formula 5, containing 25% kaolin and 25% zinc oxide, which met the required characteristics and showed the highest SPF value of 16.01. This combination of ingredients can be utilised to produce an effective and environmentally friendly loose powder sunscreen.